FAKTOR-FAKTOR YANG DIPERTIMBANGKAN MAHASISWA FAKULTAS EKONOMI UNIVERSITAS TADULAKO MENGGUNAKAN MEDIA SOSIAL INSTAGRAM SEBAGAI SARANA JUAL BELI ONLINE - WENAS, ADRINA SYULIE (Fakultas Ekonomi Universitas Tadulako, 2015)
The study determines some factors considered by the students of the Economic Faculties University Tadulako using social media Instagram as a means of buying & selling online. The sampling technique is accidental side, with 105 samples taken. Based on the analysis factors using 21 indicators, the study finds 3 factors that are considered by students in using social media Instagram as a means of buying and selling online. These factors are: 1) Online Marketing consists of F3 (Ease in business), F12 (Facilitate the search for products), F14 (There are lots of goods imported or local), F15 (to hunt many gifts), F17 (can develop the business). 2) lifestyle, includes: F2 (following the trend of lifestyle), F6 (Instagram is already a lot of users), F10 (the event to seek friendship), F11 (as the entertainment media), F21 (the advice of friends); and 3) Sales Promotion factors such as: F1 (Promotion convincing), F16 (As an advertising medium offers products or services), F19 (price offered various kinds), F20 (For media information).